The reality of using methods of evaluation for learning in the light of modern developed curricula A field study on a sample of Teachers of social studies for fourth grade in the first section - أيوب رنيم (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aims to monitor the reality of using evaluation methods of learning for social studies teachers of the fourth grade in the light of modern developed curricula. The researcher has constructed a questionnaire that included evaluation methods of learning used in evaluating social studies subject. As well, asking two questions for the aim of knowing the difficulties and obstacles limiting the usage of evaluation methods of learning and suggestions which can improve the level of the usage from teachers point of the view. The research conducted a set of results indicating the existence of a very high level usage of evaluation methods of learning by social studies teachers of the fourth grade concerning oral tests, written tests and worksheets. As Concerning the class activities, exercises, project, observation and the portfolio, they are practiced to a high degree by the teachers. The results have also shown that there are no statistically significant differences between the research medium degree members to that of the method, and its due to the number of experience years and the scientific qualification.